2016
DOI: 10.1093/humrep/dew051
|View full text |Cite
|
Sign up to set email alerts
|

Risk of severe ovarian hyperstimulation syndrome in GnRH antagonist versus GnRH agonist protocol: RCT including 1050 first IVF/ICSI cycles

Abstract: EudraCT #: 2008-005452-24. ClinicalTrial.gov: NCT00756028. Trial registration date: 18 September 2008. Date of first patient's enrolment: 14 January 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 28 publications
8
128
2
Order By: Relevance
“…Severe OHSS takes maximal concern of infertility clinicians as it may complicate up to 8.9% of crude IVF/ICSI women who were stimulated by long agonist protocol (LAP) and ovulation was triggered with conventional HCG regimen [8] as well as if not timely and efficiently treated, may be associated with severe morbidity and even mortality [1,2,3,4] . All tried preventive modalities, for OHSS occurrence, up till now didn't achieve complete prevention rather than reduce the incidence of overall all as well as severe OHSS [25] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Severe OHSS takes maximal concern of infertility clinicians as it may complicate up to 8.9% of crude IVF/ICSI women who were stimulated by long agonist protocol (LAP) and ovulation was triggered with conventional HCG regimen [8] as well as if not timely and efficiently treated, may be associated with severe morbidity and even mortality [1,2,3,4] . All tried preventive modalities, for OHSS occurrence, up till now didn't achieve complete prevention rather than reduce the incidence of overall all as well as severe OHSS [25] .…”
Section: Discussionmentioning
confidence: 99%
“…from OPU day for 4 days in combination with oral cabergoline 0.5 mg from the day of HCG triggering is superior to calcium infusion alone. The OHSS protective effect of antagonists protocol (AP) was recently demonstrated in adequately powered randomized clinical trial [8] (RCT) in crude IVF/ICSI population, where the incidence of severe OHSS in AP versus LAP 5.1% vs 8.9% with p = 0.02 ; while moderate OHSS was 10.2 vs. 15.6% with p = 0.01 and rate of hospital admission due to OHSS was lower in AP when compared with LAP (1.7% vs 3.6%, P = 0.06) as well as there is no ascetic tap in AP compared to 2% in LAP (P < 0.01). In analysis of subgroup with irregular anovulatory cycle PCOS, authors reported a development of more severe OHSS when compared to less risk, women with regular ovulatory cycles [8] , so there is a need for adequate powered RCT to explore the antagonist protocol OHSS sparing effect in women at high risk for OHSS development; namely, with high basal Antimullerian hormone (AMH), Antral follicular count (AFC) and high SE2 at ovulation triggering.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably many of the trials included in the meta-analysis were done in high-risk patients. However, recent confirmation of the efficacy of GnRH antagonists for a reduction in OHSS was obtained by an RCT of 1050 unselected women having their first treatment cycle (OR 0.43, 95% CI 0.33, 0.57) [9]. That live-birth rates were similar for both treatment arms would suggest that a GnRH antagonist protocol would be the treatment of choice for the first IVF cycle in women <40years old [9].…”
Section: Use Gonadotrophin-releasing Hormone Antagonistsmentioning
confidence: 99%